Implicit Attitudes toward the Self Over Time in Chinese Undergraduates - Yang, Qing; Zhao, Yufang; Guan, Lili; Huang, Xiting (Frontiers in Psychology, 2017)
Although the explicit attitudes of Chinese people toward the self over time are known (i.e., past = present < future), little is known about their implicit attitudes. Two studies were conducted to measure the implicit subjective temporal trajectory (STT) of Chinese undergraduates. Study 1 used a Go/No-go association task to measure participants’ implicit attitudes toward their past, present, and future selves. The obtained implicit STT was different from the explicit pattern found in former research. It showed that the future self was viewed to be identical to the present self and participants implicitly evaluated their present self as better than the past self. Since this comparison of the past and present selves suggested a cultural difference, we aimed to replicate this finding in Study 2. Using an implicit association test, we again found that the present self was more easily associated with positive valence than the past self. Overall, both studies reveal an implicitly inclining-flat STT (i.e., past < present = future) for Chinese undergraduates. Implications of this difference in explicit-implicit measures and the cultural differences of temporal self appraisals are discussed.